2023
DOI: 10.1002/smll.202207350
|View full text |Cite
|
Sign up to set email alerts
|

Oral Metal‐Free Melanin Nanozymes for Natural and Durable Targeted Treatment of Inflammatory Bowel Disease (IBD)

Abstract: Oral antioxidant nanozymes bring great promise for inflammatory bowel disease (IBD) treatment. To efficiently eliminate reactive oxygen species (ROS), various metal‐based nanozymes have been developed for the treatment of IBD but their practical applications are seriously impaired by unstable ROS‐eliminating properties and potential metal ion leakage in the digestive tract. Here, the authors for the first time propose metal‐free melanin nanozymes (MeNPs) with excellent gastrointestinal stability and biocompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…To combat these dangerous diseases, it is essential to develop creative therapeutic strategies. Nanomedicine is an innovative technology for designing and synthesizing various materials with fascinating physicochemical properties at the sub-micron level and exploiting them in the biomedical field ( Liu et al, 2022a ; Zhu et al, 2022 ; Huang et al, 2023b ; Sun et al, 2023 ). Multiple medical fields are already benefiting from the advantages offered by nanotechnology, including disease diagnosis and surveillance, cancer therapy, and regenerative medicine, etc ( van der Meel et al, 2019 ; Yang et al, 2019 ; Xu et al, 2020 ; Liu et al, 2022b ).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…To combat these dangerous diseases, it is essential to develop creative therapeutic strategies. Nanomedicine is an innovative technology for designing and synthesizing various materials with fascinating physicochemical properties at the sub-micron level and exploiting them in the biomedical field ( Liu et al, 2022a ; Zhu et al, 2022 ; Huang et al, 2023b ; Sun et al, 2023 ). Multiple medical fields are already benefiting from the advantages offered by nanotechnology, including disease diagnosis and surveillance, cancer therapy, and regenerative medicine, etc ( van der Meel et al, 2019 ; Yang et al, 2019 ; Xu et al, 2020 ; Liu et al, 2022b ).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[38] On the other hand, it was also extensively reported that TWD-based nanodrugs are being used to eliminate ROS for the treatment of acute kidney injury and inflammatory bowel disease. [33,39] The disparity in TWD's behavior is due to their differences in synthesis strategy and surface ligands. The TWDs that generate ROS are either bare or sparsely coated with ligands, making them prone to coordinate with H 2 O 2 and generate ROS via Fenton-like reactions.…”
Section: Fabrication and Characterization Of Wndsmentioning
confidence: 99%
“…60 Melanin is a biopolymer rich in antioxidant groups and endogenous free radicals. 60,83 Therefore, MMPP exhibited an excellent ROS scavenging effect, eliminating 79.4 AE 4.7% of O 2 À at a low concentration (25 mg mL À1 ), and 68.4 AE 2.5% of OH and 85.2 AE 2.3% of ABTS + at a concentration of 100 mg mL À1 (Fig. 4g-i).…”
Section: Coordination Polymer Nanodots (Cpns)mentioning
confidence: 87%